2008
DOI: 10.1029/2008jg000689
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the common signal in tree ring stable isotope chronologies at temperate sites

Abstract: [1] It is currently not well known how coherent carbon and oxygen isotope chronologies from different species and sites are under temperate climate conditions. Here we investigated nine chronologies from Switzerland covering the last two centuries, including three deciduous species (Fagus sylvatica, Fraxinus excelsior, and Quercus petraea) and three conifer species (Abies alba, Picea abies, and Pinus sylvestris) from sites neither strongly limited by temperature nor precipitation. All of the chronologies excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
73
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 65 publications
11
73
2
1
Order By: Relevance
“…First, the improvements in considering regionally averaged d 18 O from GNIP rather than those at individual stations illustrates the utility of combining multiple, targeted, isotopic archives across a given region. This technique has been applied for Greenland ice cores [White et al, 1997;Rogers et al, 1998] and for tree cellulose [Treydte et al, 2007;Saurer et al, 2008] [36] The NAM-like expression was identified through an empirical analysis of the controls rather than with a single circulation index and a priori assumption of the dominant control. Indeed, as Hurrell et al…”
Section: Implications For Paleoclimate Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the improvements in considering regionally averaged d 18 O from GNIP rather than those at individual stations illustrates the utility of combining multiple, targeted, isotopic archives across a given region. This technique has been applied for Greenland ice cores [White et al, 1997;Rogers et al, 1998] and for tree cellulose [Treydte et al, 2007;Saurer et al, 2008] [36] The NAM-like expression was identified through an empirical analysis of the controls rather than with a single circulation index and a priori assumption of the dominant control. Indeed, as Hurrell et al…”
Section: Implications For Paleoclimate Reconstructionmentioning
confidence: 99%
“…O record, providing a complementary source of reconstruction information [McDermott, 2004;Saurer et al, 2008;Lachniet, 2009].…”
mentioning
confidence: 99%
“…Drought effects in forests can be enhanced by intraspecific or interspecific competition for water (Gouveia and Freitas 2008) which may be reflected in the chronology of annual tree rings (Saurer et al 2008). Another archive of environmental changes is the tree-ring d 13 C signature.…”
Section: Introductionmentioning
confidence: 99%
“…Both mechanisms can have consequences for tree growth and the d 13 C signature in the annual rings. Thus, long-term records of these growth and water status proxies can provide valuable insight into a tree's long-term water regime and possibly also into competition-induced changes of the water balance (McNulty and Swank 1995;Buchmann et al 1997;Skomarkova et al 2006;Grams et al 2007;Saurer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although strong correlations between isotopic and instrumental data from temperate areas such as Britain (Loader et al, 2003;Loader et al, 2008;Robertson et al, 1997b), Northern France (Etien et al, 2009), Southern Finland (Hilasvuori & Berninger, 2010 and Swiss Central Plateau (Saurer et al, 2008) were evaluated, and only one publication concerning the climate reconstruction of the site neither strongly limited by temperature nor precipitation (temperature in Central England) (Young et al, 2012) was found.…”
Section: Introductionmentioning
confidence: 99%